Analytical Study of Soret and Dufour effect in the Electro-osmotic peristaltic flow of Rabinowitsch fluid model - Hasen, Saba S.; Abdulhadi, Ahmed M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The present paper concerned with study the of combined electro-osmotic peristaltic transport with heat and mass transfer which is represented by the Soret and Dufour phenomenon with the presence of the Joule electrothermal heating through a microchannel occupy by Rabinowitsch fluid. The unsteady two-dimensional governing equations for flow with energy and concentration conservation have been formed in a Cartesian coordinate system and the lubrication theory is applied to modify the relevant equations to the problem. The Debye-Hukel linearization approximation is utilizing to modify the electrohydrodynamics problem. The expressions for the axial velocity, the temperature profile, the concentration profile, and the volumetric flow rate are obtained analytically to gain exact solutions, while the numerical integration is used to analyze the pressure rise. The attitude of the Helmholtz-Smoluchowski velocity, the electro-osmotic parameter, the Joule electrothermal heating, the Dufour number, the Soret number, is studied and graphically analyzed. It is showed that the presence of the electric field increased the velocity of the fluid and pressure rise, and it is revealed that the temperature and concentration profile congregate in the center of the channel with increase in the Soret and Dufour number.